Multidecadal Changes in Marine Subsurface Oxygenation Off Central Peru During the Last ca. 170 Years - Cardich, J (2019)
Subsurface water masses with permanent oxygen deficiency (oxygen minimum zones,OMZ) are typically associated with upwelling regions and exhibit a high sensitivity to climate variability. Over the last decade, several studies have reported a global ocean deoxygenation trend since 1960 and a consequent OMZ expansion.